Liver transplantation in critically ill patients: Preoperative predictive factors of post‐transplant mortality to avoid futility. Issue 12 (31st October 2017) - Michard, Baptiste; Artzner, Thierry; Lebas, Benjamin; Besch, Camille; Guillot, Max; Faitot, François; Lefebvre, François; Bachellier, Philippe; Castelain, Vincent; Maestraggi, Quentin; Schneider, Francis
Abstract: Background: The allocation of liver transplants to patients with acute liver failure (ALF) and acute‐on‐chronic liver failure (ACLF) with multi‐organ failure who are admitted in ICU remains controversial due to their high post‐transplant mortality rate and the absence of identified mortality risk factors. Methods: We performed a single‐center retrospective cohort study to determine the post‐transplant mortality rate of patients with ALF and ACLF requiring ICU care prior to liver transplant (LT) and identified pretransplant factors of post‐transplant mortality. Results: Eighty‐four patients (29 with ALF and 55 with ACLF) received a liver transplant while they were hospitalized at the ICU. Their mean model for end‐stage liver disease (MELD) score was 41, and their mean sequential organ failure assessment (SOFA) was 15 the day before transplant. The overall 1‐year survival rate was 66%. In multivariate analysis, pretransplant lactate level and acute respiratory distress syndrome (ARDS) were the only two independent factors associated with post‐transplant mortality. The absence of ARDS and a pretransplant lactate level< 5 mmol/L led to the identification of a subgroup of ICU patients with a good 1‐year post‐transplant survival (>80%). Conclusions: Low lactatemia lactate level and the absence of ARDS could be useful criteria in selecting those patients in ICU who could be eligible for liver transplant.